Counseling Interventions for Academic Stress in Students: A Systematic Literature Review Using PRISMA 2020 Guidelines - Latifah Dewi Indriyani; Anni Suprapti; Mayang T. Afriwilda (Indonesian Journal of Counseling and Development, 2026)
Academic stress constitutes a pervasive global challenge with measurable consequences for students' psychological well-being and academic performance. Despite the proliferation of counseling interventions across diverse educational contexts, a comprehensive synthesis of their effectiveness and cross-cultural applicability remains limited. This study aims to identify global trends of effective counseling interventions to deal with students' academic stress at various levels of education. The study used the Systematic Literature Review (SLR) method by following the guidelines of Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) through a literature search in the Scopus database. The initial identification process resulted in 269 articles published in the range of 2020-2025, and after going through a gradual process, there were 10 articles that met the criteria for analysis. The findings show that various interventions such as Cognitive Behavioral Therapy, Mindfulness, Group Counseling, Stress Management Programs, and Commitment Therapy have been proven to be effective in reducing students' academic stress. Among these, MBI emerged as a promising approach with consistent positive outcomes across multiple cultural contexts, evidenced by significant effect sizes (e.g., d=0.62–0.84) in three independent studies conducted in Indonesia, the United States, and China. These findings can be a reference for counselors in implementing evidence-based counseling services through group formats and digital platforms that are in accordance with the cultural context of students.